The Value of Srikandi Mustakaweni Act in Wayang Wong Bocah Tjipta Boedaja Residence Magelang - Amsari, Uli; Cahyono, Agus; Hartono, Hartono (Catharsis, 2019)
Wayang Wong Bocah in Tjipta Boedaja Residence is one of the performing arts filled with value and relevant to be inculcated for children. Wayang Wong Bocah is performed by children. The purpose of this research is to analyze and describe the inculcation of value through Wayang Wong Bocah performance with Srikandi Mustakaweni act. Qualitative method with ethno-choreology and arts education approaches were used in this research. The data were collected through observation, interview, and documentary study. The data were validated using investigators triangulation technique, and analyzed by discribing, discreening, interpreting, and evaluating. The result shows that inculcation of value for children can be done through plot and model performed by children. Plot helps them to learn about good or bad, while model helps them distinguish an exemplary behavior as shown by Srikandi who was responsible, and not exemplary behavior as shown by Mustakaweni who was dishonest. The values that appear in the story such as honesty, responsibility, curiosity, patriotism, peacefulness, and hard-work. It is concluded that those values can be the guidelines about good or bad for children. Those values are expected to be implemented in daily basis.